2008
DOI: 10.1111/j.1365-2044.2007.05414.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lidocaine on remifentanil‐induced cough

Abstract: SummaryThis study was performed to investigate the incidence of remifentanil-induced cough and evaluate the efficacy of lidocaine on its prevention. Five-hundred patients, aged 18-70 years, were randomly allocated into two groups to receive either lidocaine 0.5 mg.kg )1 or 0.9% normal saline intravenously 1 min before remifentanil administration at a target effect-site concentration of 4 ng.ml )1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 21 publications
5
47
3
Order By: Relevance
“…In the present study, when remifentanil's effect site concentration was set at 4.0 ng/ml, the incidence of coughing was 34%, which is slightly higher than that reported by Kim et al [2,3] who set the effect site concentration at 4.0 ng/ml and 5.0 ng/ml and the incidence of coughing was 27.6% and 27.9%, respectively. The difference is believed to be caused by the different characteristics of the subjects of the two studies.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…In the present study, when remifentanil's effect site concentration was set at 4.0 ng/ml, the incidence of coughing was 34%, which is slightly higher than that reported by Kim et al [2,3] who set the effect site concentration at 4.0 ng/ml and 5.0 ng/ml and the incidence of coughing was 27.6% and 27.9%, respectively. The difference is believed to be caused by the different characteristics of the subjects of the two studies.…”
Section: Discussioncontrasting
confidence: 75%
“…There have been reports showing that smoking reduced the incidence of fentanyl-induced coughing [9,10]. Kim et al reported that the incidence of remifentanil induced coughing was lower in smokers than that in nonsmokers [2]. Therefore, the higher incidence of coughing in our study is considered to be due to the exclusion of smokers.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations